Analiza programów niemieckiej chadecji na wybory do Parlamentu Europejskiego w kontekście problemów, zagrożeń i zmian występujących w Unii Europejskiej w latach 2009-2019 = Analysis of the programs of the German Christian Democrats for elections to the European Parliament in the context of problems, threats and changes occurring in the European Union in 2009-2019 - Bielawska, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the position of the German Christian Democrats (Ger. Christlich-Demokratische Union Deutschlands, CDU and Christlich-Soziale Union, CSU) towards the changes, problems and threats emerging in the European Union and in the Member States. It analyzes the election programs for the elections to the European Parliament and the statements of leading representatives of the CDU and CSU. The article is divided into two parts - the backstage of the creation of election programs to the EP and the changes proposed in the Christian Democratic programs for the elections to the EP in 2009-2019.
Keywords: CDU; CSU; polityka europejska; wybory; Parlament Europejski; Unia Europejska; European policy; elections to the European Parliament; European Union